2002
DOI: 10.1097/00005053-200205000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties and Concurrent Validity of the Schizotypal Ambivalence Scale

Abstract: The Schizotypal Ambivalence Scale (SAS) is a 19-item revision of the Intense Ambivalence Scale, which was designed to identify ambivalence described by Meehl as characteristic of schizotypy and schizophrenia. The present study examined the psychometric properties of the SAS in a sample of 997 college students. The study also provided preliminary evidence regarding the concurrent validity of the measure for identifying schizophreniclike symptoms and other forms of psychopathology in a sample of 131 students. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
34
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 16 publications
6
34
0
Order By: Relevance
“…For instance, across several types of emotionally evocative stimuli (pictures, words, and sounds) Trémeau et al (2009) found that while participants with and without schizophrenia reported similar stimulus-congruent emotion ratings, schizophrenia participants reported higher stimulus-incongruent emotion to both positive and negative stimuli. These lab findings are supported by self-report studies finding that psychosis may be associated with higher trait ambivalence (Kwapil et al, 2002; Kerns, 2006; Kerns and Becker, 2008). …”
Section: Introductionsupporting
confidence: 68%
“…For instance, across several types of emotionally evocative stimuli (pictures, words, and sounds) Trémeau et al (2009) found that while participants with and without schizophrenia reported similar stimulus-congruent emotion ratings, schizophrenia participants reported higher stimulus-incongruent emotion to both positive and negative stimuli. These lab findings are supported by self-report studies finding that psychosis may be associated with higher trait ambivalence (Kwapil et al, 2002; Kerns, 2006; Kerns and Becker, 2008). …”
Section: Introductionsupporting
confidence: 68%
“…In contrast, the rSAmb has not been associated with major depressive disorder (Kwapil et al., 2002; Mann et al, 2008), although rates of major depression or other forms of clinical disorders were low in these nonclinical samples. At the same time, the rSAmb has been strongly associated with decreased emotional clarity (Cicero and Kerns, 2010; Kerns, 2006), which has also been strongly associated with depression (Berenbaum et al, 2012; Salovey et al, 1995).…”
mentioning
confidence: 60%
“…The SAS is a 19-item revision of the Intense ambivalence scale, which was designed to identify ambivalence, described by Meehl as characteristic of schizotypy and schizophrenia (Raulin, [10]; Kwapil et al, [25]). Satisfactory internal consistency and reliability in different samples of college students or young adults have been reported (Raulin, [10]; Kwapil et al, [25]). We used the French versions of the CSS and SAS that present satisfactory psychometric properties (Yon et al, [34]).…”
Section: Methods and Resultsmentioning
confidence: 99%
“…In the second study [23], subjects with disorganized schizotypy significantly differed from control participants in terms of emotional ambivalence measured by the Schizotypal Ambivalence Scale [25]. …”
Section: Introductionmentioning
confidence: 99%